Study the Pattern of D-Dimers, HS CRP and Ferritin in Covid-19 Patients - Rehma Dar, Rabia Butt, Fauzia Sadiq, Mazhar Fareed, Lubna Shaheen, Maham Shakoor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Corona virus disease is caused by SARS-CoV-2. This pandemic has affected over 200 countries. Most of the patients are asymptomatic. The disease is usually mild but in approximately 14% of patients it worsens to severe respiratory impairment and admission to ICU. Different tests in laboratories have been used to assess severity and prognosis of severely sick Covid-19 patients in addition to clinical and radiological findings. Aim: To study pattern of Hs- CRP, Ferritin and D-Dimers in Covid-19 patients admitted in Mayo Hospital/ KEMU Duration: June 2020 to October, 2020. Methods: It was a descriptive study conducted in Central Diagnostic Laboratory (CDL) of Mayo Hospital/ KEMU, Lahore on 1474 Covid-19 patients. All samples of the Covid-19 patients sent to CDL of Mayo hospital/ KEMU Lahore for D-Dimers, Hs CRP and Ferritin levels were included in the study. The results and other relevant information were recorded on proforma. The collected data was analyzed by SPSS 23.Quantitative variables like age was presented as mean ± SD. Qualitative variables like gender, single, double or triple parameter abnormalities were presented as frequency and percentage. Results: Out of total 1474, 958(65%) samples were of male and 516(35%) were of female patients. Mean age± SD was50.6±4.2 years. The percentage of abnormal Hs CRP, D Dimers and ferritin was 1386(94%), 1312(89%) and 1135(77%) respectively. The mean±SD value for HsCRP, D-Dimers and ferritin was 56.8±16.9mg/L, 4.4±1.5µg/ml FEU and 770±180 ng/ml respectively. The patients having 3, 2 and 1 abnormal parameter were 988(67%), 456(31%) and 29(2%). Conclusion: Males were more affected with Covid-19 as compared to females. HsCRP is the most frequently raised biomarker in Covid-19 patients and both inflammatory (HsCRP and Ferritin) and coagulopathy marker (D Dimers) were raised in severely sick Covid-19 patients. Keywords: D Dimers, Ferritin, Hs CRP, Covid-19 patients.